Tamdy Virus in Ixodid Ticks Infesting Bactrian Camels, Xinjiang, China, 2018 - Hong Zhou; Zhenghai Ma; Tao Hu; Yuhai Bi; Amutikari Mamuti; Runyuan Yu; Michael J. Carr; Mang Shi; Juan Li; Kirill Sharshov; George F. Gao; Weifeng Shi (Emerging Infectious Diseases, 2019)
We isolated Tamdy virus (TAMV; strain XJ01/TAMV/China/2018) from Hyalomma asiaticum ticks infesting Bactrian camels in Xinjiang, China, in 2018. The genome of the strain showed high nucleotide similarity with previously described TAMV strains from Asia. Our study highlights the potential threat of TAMV to public health in China.